Adapting the Capability Approach to Explain the Effects of Participatory DevelopmentPrograms: Case Studies from India and Morocco - SONY PELLISSERY and SYLVIA I. BERGH (Journal of Human Development Vol. 8, No. 2, July 2007, 2007)
This paper attempts to explore the linkages between democracy, participation, and inequality. It does so by situating the role of `public scrutiny and debate' in Sen's work. It then draws on the literature on `deliberative democracy' to show the linkages between requirements for (ideal, democratic) political participation and typologies of participation that have emerged in the development context. It finally links this discussion to concepts of power and inequality. Three case studies help to illustrate the use of this analytical framework. The Employment Guarantee Scheme case study from the Indian state of Maharashtra illustrates the effects of `participation for material incentives' built on both `hidden' and `invisible power' structures. The Moroccan casestudy shows the potential for participatory approaches to deepen existing inequalities when certain pre-conditions for participation are not fulfilled, leading to `hidden power' domination. The Kerala case study is an example for political participation that is built on `visible' power strategies. Hence, this paper attempts to contribute to the discussion on the intended and unintended effects of participatory schemes by developing andapplying a more comprehensive analytical framework